Neoadjuvant Weekly Carboplatin and Paclitaxel Followed by Radical Hysterectomy for Locally Advanced Cervical Cancer: Long-Term Results. Issue 4 (1st May 2010) - Mori, Taisuke; Hosokawa, Kenichi; Sawada, Morio; Kuroboshi, Haruo; Tatsumi, Hiroshi; Koshiba, Hisato; Okubo, Tomoharu; Kitawaki, Jo
Abstract : Introduction: To determine the long-term effect of neoadjuvant chemotherapy with paclitaxel and carboplatin on a weekly schedule followed by radical surgery for patients with locally advanced cervical cancer. Materials and Methods: Thirty patients with stage IB2 to IIIB uterine cervical cancer were treated with paclitaxel (60 mg/m 2 ) and carboplatin (area under the curve, 2-an area under the time-concentration curve of 2 mg × min/mL based on creatinine clearance) every week for 6 cycles. A radical hysterectomy was performed 6 days after the final administration of neoadjuvant chemotherapy. The patients were followed up, and 5-year progression-free survival (PFS) and overall survival (OS) were evaluated. Results: Of 30 patients, 28 were followed up. The median follow-up period was 55.6 months (range, 26-83 months). An objective response (complete response + partial response) to the treatment was observed in 26 patients (87%; 95% confidence interval, 70%-95%). Two had complete response, 4 had stable disease, and the remaining patients had partial response; progressive disease was not seen in this study. A radical hysterectomy was performed in 28 patients without delay. Thirteen patients with high-risk factors received radiotherapy after surgery. The 5-year PFS and OS rates were 78.6% and 81.8%, respectively. The 5-year PFS and OS for patients with stage IB2 to IIB cervical cancer were 79.2% and 83.1%, respectively, which were comparable with those in the concurrent chemoradiation therapy study previously reported. There was no significant correlation in survival between preoperative staging and cell type, whereas larger initial tumor size and lymph node metastasis tended to be negatively correlated with survival. Conclusions: Neoadjuvant chemotherapy with paclitaxel and carboplatin on a weekly schedule followed by radical surgery for patients with locally advanced cervical cancer is a promising mode of therapy that may improve the prognosis. It would be worthwhile to conduct larger-scale trials for comparison with the results of the chemoradiation therapy study.